A Novel Setup for the Controlled Adduction of Vocal Folds - Gedeon, Dominik; Rupitsch, Stefan; Lerch, Reinhard; Luegmair, Georg; Döllinger, Michael (Mechatronics 2012 - The 13th Mechatronics Forum International Conference, 2012)

Development of a time-dependent numerical model for the assessment of non-stationary pharyngoesophageal tissue vibrations after total laryngectomy - Hüttner, Björn; Luegmair, Georg; Patel, Rita R.; Ziethe, Anke; Eysholdt, Ulrich; Bohr, Christopher; Sebova, Irina; Semmler, Marion; Döllinger, Michael (Biomechanics and Modeling in Mechanobiology, 2015)
Laryngeal cancer due to, e.g., extensive smoking and/or alcohol consumption can necessitate the excision of the entire larynx. After such a total laryngectomy, the voice generating structures are lost and with that the quality of life of the concerning patients is drastically reduced. However, the vibrations of the remaining tissue in the so called pharyngoesophageal (PE) segment can be applied as alternative sound generator. Tissue, scar, and geometric aspects of the PE-segment determine the postoperative substitute voice characteristic, being highly important for the future live of the patient. So far, PE-dynamics are simulated by a biomechanical model which is restricted to stationary vibrations, i.e., variations in pitch and amplitude cannot be handled. In order to investigate the dynamical range of PE-vibrations, knowledge about the temporal processes during substitute voice production is of crucial interest. Thus, time-dependent model parameters are suggested in order to quantify non-stationary PE-vibrations and drawing conclusions on the temporal characteristics of tissue stiffness, oscillating mass, pressure, and geometric distributions within the PE-segment. To adapt the numerical model to the PE-vibrations, an automatic, block-based optimization procedure is applied, comprising a combined global and local optimization approach. The suggested optimization procedure is validated with 75 synthetic data sets, simulating non-stationary oscillations of differently shaped PE-segments. The application to four high-speed recordings is shown and discussed. The correlation between model and PE-dynamics is [Formula: see text] 97 %.
EVALuna2:19926

Optical 3-D Metric Measurements of Local Vocal Fold Deformation Characteristics in an In Vitro Setup - Hüttner, Björn; Sutor, Alexander; Luegmair, Georg; Rupitsch, Stefan; Lerch, Reinhard; Döllinger, Michael (IEEE Transactions on Biomedical Engineering, 2011)
Understanding vocal fold dynamics presents an essential part in treating voice disorders as it is the prerequisite to appropriate medical therapy. Various physical and numerical models exist for simulation purposes, all relying on simplified material parameters. To improve current approaches, data of realistic tissue behavior, i.e., in natural surroundings, have to be considered in model development. An in vitro setup was proposed for tensile tests combined with an optical method for precise, local and metrical 3-D measurements of distinctive surface points. Compared to previous 3-D reconstruction methods, the accuracy was improved tenfold. Vertically applied forces versus resulting deformation were measured for ten porcine vocal folds. Deformation characteristics of mucosa and the two-layer structure of mucosa and muscle (MM) were investigated at three distinctive locations along the vocal fold edge. The spring rates were represented by an exponential function. For equal deflections, an increasing spring rate from posterior to anterior for MM was measured. For solely mucosa, the spring rate decreased from the posterior to the middle and subsequently increased again. The MM-layer presented a stiffer deformation behavior than mucosa. For deformations higher than 1.5 mm, the spring rates for MM were more than twice as high as for mucosa. The investigations display the importance of considering both multilayers and local differences for the improvement of vocal fold models.
Keywords: Image processing; optical measurement; stereo triangulation; tensile test; vocal fold deformation characteristics

Optical Reconstruction of High-Speed Surface Dynamics in an Uncontrollable Environment - Luegmair, Georg; Kniesburges, Stefan; Zimmermann, Maik; Sutor, Alexander; Eysholdt, Ulrich; Döllinger, Michael (IEEE Transactions on Medical Imaging, 2010)
The ability to communicate with our voice can be regarded as the concatenation of the two processes "phonation" and "modulation." These take place in the larynx and palatal and oral region, respectively. During phonation the audible primary voice signal is created by mutual reaction of vocal folds with the exhaled air stream of the lungs. The underlying interactions of masses, fluids and acoustics have yet to be identified and understood. One part of the primary signal's acoustical source are vortex induced vibrations, as e. g., created by the Coandaeffect in the air stream. The development of these vorteces is determined by the shape and 3-D movements of the vocal folds in the larynx. Current clinical in vivo research methods for vocal folds do not deliver data of satisfactory quality for fundamental research, e. g., an endoscope is limited to 2-D image information. Based hereupon, a few improved methods have been presented, however delivering only selective 3-D information, either for a single point or a line. This stands in contrast to the 3-D motions of the entire vocal fold surface. More complex imaging methods, such as MRI, do not deliver information in real-time. Thus, it is necessary to develop an easily applicable, more improved examination method, which allows for 3-D data of the vocal folds surfaces to be obtained. We present a method to calibrate a 3-D reconstruction setup including a laser projection system and a high-speed camera. The setup is designed with miniaturization and an in vivo application in mind. The laser projection system generates a divergent grid of 196 laser dots by diffraction gratings. It is calibrated with a planar calibration target through planar homography. In general, the setup allows to reconstruct the topology of a surface at high frame rates (up to 4000 frames per second) and in uncontrollable environments, as e. g., given by the lighting situation (little to no ambient light) and varying texture (e. g., varying grade of reflection) in the human larynx. In particular, this system measures the 3-D vocal fold surface dynamics during phonation. Applied to synthetic data, the calibration is shown to be robust (error approximately 0.5 mu m) regarding noise and systematic errors. Experimental data gained with a linear z-stage proved that the system reconstructs the 3-D coordinates of points with an error at approximately 15 mu m. The method was applied exemplarily to reconstruct porcine and artificial vocal folds' surfaces during phonation. Local differences such as asymmetry between left and right fold dynamics, as well as global parameters, such as opening and closing speed and maximum displacements, were identified and quantified.
Keywords: Biomedical imaging; laser projection system calibration; planar homography; surface reconstruction

Preliminary results on the influence of engineered artificial mucus layer on phonation - Döllinger, Michael; Gröhn, Franziska; Berry, David A.; Eysholdt, Ulrich; Luegmair, Georg (Journal of Speech Language and Hearing Research, 2014)
PURPOSE Previous studies have confirmed the influence of dehydration and an altered mucus (e.g., due to pathologies) on phonation. However, the underlying reasons for these influences are not fully understood. This study was a preliminary inquiry into the influences of mucus architecture and concentration on vocal fold oscillation. METHOD Two excised human larynges were investigated in an in vitro setup. The oscillations of the vocal folds at various airflow volume rates were recorded through the use of high-speed imaging. Engineered mucus containing polymers (interconnected polymers and linear polymers) was applied to the vocal folds. From the high-speed footage, glottal parameters were extracted through the use of objective methods and were compared to a gold standard (physiological saline solution). RESULTS Variations were found for all applications of mucus. Fundamental frequency dropped and the oscillatory behavior (speed quotient [SQ], closing quotient [CQ]) changed for both larynges. The 2 applied mucus architectures displayed different effects on the larynges. The interconnected polymer displayed clear low-pass filter characteristics not found for the linear polymer. Increase of polymer concentration affected parameters to a certain point. CONCLUSION The data confirm results found in previous studies. Furthermore, the different effects-comparing architecture and concentration-suggest that, in the future, synthetic mucus can be designed to improve phonation.
EVALuna2:20187